KONTRIBUSI GERAKAN USAHA PEMBARUAN PENDIDIKAN ISLAM (GUPPI) TERHADAP PEMBAHARUAN PENDIDIKAN ISLAM DAN PENGEMBANGAN DAKWAH - Muh Ilham (Jurnal Dakwah Tabligh, 2016)
This study discusses the efforts GUPPI in the reform of Islamic education and the contribution GUPPI in education reform effort Islam.The eimed this study was to determine the effort GUPPI in Islamic education reform effort and to determine the contribution GUPPI in the reform of Islamic education. This type of research is a field research (field research) are implemented in Gowa. This research is descriptive qualitative, using the sociological approach, historical and anthropological. Data collected through observation, interviews and documentation. Sources of data obtained through primary data and secondary data. The data obtained are then processed in a deductive, inductive and comparative then presented, is reduced and verified as well as the conclusion. The results showed that, GUPPI efforts in the improvement of education is to adapt the curriculum with the curriculum in force at the National Education Ministry, improve infrastructure, and to add teachers and improve the welfare of teachers' honorarium. Contributions GUPPI in an attempt to reform Islam is to develop the organization as a means of improving and developing faith and righteous deeds, GUPPI increasing role in the implementation of Law Number. 20 of 2003 on National Education System. Realizing the social value system that is capable of filtering and National anticipate cultural values of national and global as well as seek advice and guidance facilities and  mosque in vocational schools and general principles of spontaneous and self-help.